Timeliness of routine childhood vaccinations in Indonesian infants in the first year of life - Oktaria, Vicka (Elsevier Ltd, 2022)
Background: Vaccines have proven to be one of the most effective strategies to control infectious diseases and contributed to childhood survival. While high vaccine coverages provide individual's and herd immunity, age-appropriate vaccination or vaccine timeliness is important for maximum vaccine's protection, but often not evaluated. We aimed to describe the timeliness of childhood vaccination for Indonesian infants and identify risk factors associated with delayed vaccination. Methods: This study was a sub-study of the Indonesian Pneumonia and Vitamin D status (IPAD) study, a community-based cohort study to investigate pneumonia incidence in two districts in Yogyakarta province, Indonesia. Socio-demographic data were obtained from structured interviews and vaccine status was obtained from maternal and child health records. Timely vaccination was defined if the vaccine was received between four days or less before and within 28 days after the recommended age of vaccination. Results: 359 (85) out of 422 IPAD participants and their immunisation records were included. Between December 2015 and December 2017, vaccination coverage was high and ranged from 96.1 (Measles) to 100 (DTP-HepB-Hib 1). However, two thirds (67, 242/359) of all participants had received either early or late vaccines, with dose 2 IPV (40, 143/356), dose 3 IPV (56, 196/349) and dose 3 DTP-HepB-Hib (29, 103/354) most delayed, and only 1 received early doses. The main risk factors for untimely vaccination were if the infant was born in a private practice versus in a public health facility (AOR 1.90; 95 CI: 1.18–3.07) and rural residence (AOR 1.84; 95 CI: 1.15–2.94). Conclusions: Despite high vaccine coverage for Indonesian infants (>95), two thirds (67) of infants had untimely vaccinations, with dose 3 IPV (56) the most delayed. Future strategies should focus on coordination between government, health care providers, and carers to ensure timely access and vaccination of infants to ensure adherence to vaccination schedules. © 2022 Elsevier Ltd